Homoseksualiteit als fiktie - van Gils, Wouter; Jeurissen, Luc; Thomassen, Yvonne (Tilburg : Katholieke Hogeschool Tilburg, 1982)
Fonds Suzan Daniel (FSD)
Nederlands
Monografie
Keywords: homoseksualiteit